Aromatherapy Effectivity in Controlling Anxiety, Respiration Rate, Pulse Rate, and Pain in Bronchoscopy - Nur Amalia Santang; Yusup Subagio Sutanto; Debree Septiawan (Respiratory Science, 2023)
ackground: Bronchoscopy is a relatively safe diagnostic and therapeutic procedure, but it is often reported as an uncomfortable experience and causes acute procedural anxiety that affects the procedure and the patient and operator's comfort. Anti-anxiety drugs have the risk of causing mild to severe side effects. Therefore, we need premedication with potent anxiolytics with minimal side effects, such as the use of aromatherapy. This study aims to analyze the effectiveness of aromatherapy as an additional premedication to reduce anxiety, respiratory rate, pulse rate, and pain in patients undergoing bronchoscopy. Method: A clinical study with experimental quasi pre-post test control group design using consecutive sampling was performed in pulmonary patients undergoing bronchoscopy in dr. Moewardi Hospital from February to March 2020. The study subjects were randomized into three groups: lavender aromatherapy, orange aromatherapy, and control. Hospital anxiety and depression scale (HADS) score, respiratory rate, pulse, and visual analogue scale (VAS) pain score were measured before and after bronchoscopy.  Results: A total of 45 subjects of lung patients undergoing bronchoscopy participated in this study. Post hoc test differences in the HADS anxiety score of lavender and orange groups showed a significant decrease (P=0.011); (P=0.083), respectively. The decrease in the control group was not significant (P=0.622). There was a significant decrease in the respiratory rate of lavender (P≤0.0001), and orange groups (P=0.001), while the control group did not decrease (P=0.515). There was a significant decrease in pulse rate in the lavender (P=0.004) and orange (P=0.011) groups. The decrease in the control group was not significant (P=0.900). There was a significant decrease in VAS pain scores in the lavender and orange groups with each (P<0.001), whereas, in the control group, there was an increase in VAS pain scores. Conclusion: Aromatherapy effectively controls anxiety, respiration rate, pulse, and pain in bronchoscopy patients.